The relevance of the EU banking sector to economic growth and the recent financial crisis - Ferreira, Cândida (2015)
Using static and dynamic panel estimates in a sample including all 28 European Union countries during the last decade, this paper seeks to improve upon the existing literature with empirical evidence on the important role that well-functioning EU banking institutions can play in promoting economic growth. The banking sector performance is proxied by the evolution of some relevant financial ratios and economic growth is represented by the annual Gross Domestic Product growth rate. In order to analyse the possible differences arising after the outbreak of the recent international financial crisis, the estimations consider two panels: one for the time period 1998– 2012 and another for the subinterval 2007–2012. The results obtained allow us to draw conclusions not only on the importance of the variation of different operational, capital, liquidity and assets quality financial ratios to economic growth but also on some differences evidenced in the two considered panels, reflecting the consequences of the recent financial crisis and the correspondent reactions of the European banking institutions.